Arquetipo de muerte: un estudio en jóvenes mexicanos desde la perspectiva de Carl Gustav Jung (2021)
The objective of this research was to analyze the archetype of death found in the collective unconscious of the young adults of Saltillo, who have had near death experienced, either directly or through a close relative. There were four participants: 2 women and 4 men, with ages ranging from 24 to 29. The technique used for collecting information was an in-depth interview. The interviews were conducted individually and in a session with each participant. Only one subject's interview was conducted in two sessions due to the amount of information. An analysis of the discourse with a hermeneutic approach was developed, guided by the interpretation theory of Paul Ricœur (2003). Three categories of analysis were made: the concept of death, beliefs about death, characteristics about death. At the time of categorizing the information, it was decided to add one more category, which is that of emotions and feelings about death